Development of GeoGebra-Assisted Learning Media to Improve Students' Mathematical Problem-Solving Skills in Transformational Geometry in Junior High School - Majid Majid; Swasti Maharani; Kartin Usman (Sakura Digital Nusantara, 2026)
Purpose: The purpose of this project is to create GeoGebra-assisted learning materials for transformation subjects and to assess their efficacy, validity, and usefulness in enhancing students' mathematical problem-solving abilities. Methods: The five steps of the ADDIE model analysis, design, development, implementation, and evaluation were used in this study's Research and Development (R&D) methodology. Experts in media and materials verified the product, and SMP Negeri 3 Suwawa students in Grade IX participated in both small-scale and large-scale trials. Validation sheets, response surveys, and tests of problem-solving abilities were used to gather data. Gain score analysis and pretest-posttest scores were used to gauge the media's efficacy. Findings: The findings demonstrated that the GeoGebra-assisted learning resources satisfied the requirements for efficacy, practicality, and validity. The product's viability for use in mathematics education was confirmed by expert validation. In both the small-scale and large-scale trials, student replies were 88.90% and 89.23%, respectively, while instructor responses were 95.2%, both of which were classified as extremely practical. The effectiveness test showed that students' ability to solve mathematical problems had significantly improved, as evidenced by the average pretest score rising from 53.33 to 89.89 in the posttest. A high and successful degree of improvement was indicated by the gain score of 0.71 and the gain percentage of 70.74%. Research implications: The created educational materials can be a useful substitute for teaching mathematics, especially when it comes to transformation subjects that call for powerful visualisation. GeoGebra integration offers interactive learning opportunities that improve students' problem-solving skills and help them grasp concepts. Originality: By creating and validating a GeoGebra-assisted learning medium especially for transformation material and methodically assessing its quality using validity, practicality, and effectiveness criteria within the ADDIE development framework, this study advances mathematics education.